Inventering av röjningsobjekt från helikopter - Zethraeus, Fredrik (SLU/Southern Swedish Forest Research Centre, 2007)
In time with HolmenSkog district Egenskog Norrköping´s decreasing mountain of cleaning, the office started to look around for new alternative cleaning strategies to lower the costs connected with cleaning. One option was to make the inventory strategy more effective and after a phonecall with the head of the district, Jonnie Friberg, the planning started to try inventory in pictures taken from a helicopter. The pictures was at last taken from a digtal camera and the vegetationheight was mesured with a laser. The gear was supplied from Kallax Flyg AB, Luleå. In the trial 15 stands was selected depended on age and different mixtures between pine (Pinus sylvestris), spruce (Picea abies) and birch (Betula pubescense and Betula pendula). Eatch pictures was about 300 – 400 m2 and was divided in to nine equal squares with the aerial discription in m2. The vegetationheight was mesured in profiles. The result showed that no systematic deflection was found if the total number of stems was <6000 st/ha. To get the standard error (SE) from the pictures to be comparable with the traditional method used for inventery, we needed 6-10 pictures for each stand depending on the area. The SE for vegetationheight was between 0,1 to 0,8 m and for the traditional method 0,1 to 1,2 m. In the pictures three of the nine squares was counted, and it was an acceptable accuracy. So in this studie the costs for the helicopter method was 110 SEK ha-1, and for the traditional method 155 SEK ha-1. I takt med att Holmen Skog, distrikt Egenskog i Norrköping, började bli färdiga med det röjningsberg som funnits såg sig kontoret om efter alternativa röjningsstrategier för att sänka kostnaderna i samband med röjning. Ett av alternativen var att effektivisera inventeringsmetoderna och efter ett samtal med distriktschef Jonnie Friberg började planeringen för att inventera i bilder tagna ifrån helikopter. Metoden som till slut användes var en gyroupphängd lodkamera med en laserhöjdmätare för höjdmätning av beståndet och denna utrustning ...